A Cadaveric Study of the Thread Trigger Finger Release: The First Annular Pulley Transection Through Thread Transecting Technique. (March 2018) - Guo, Danqing; Guo, Danzhu; Guo, Joseph; McCool, Logan C.; Tonkin, Brionn
Background: After the thread transecting technique was successfully applied for the thread carpal tunnel release, we researched using the same technique in the thread trigger finger release (TTFR). This study was designed to test the operational feasibility of the TTFR on cadavers and verify the limits of division on the first annular (A1) pulley to ensure a complete trigger finger release with minimal iatrogenic injuries.Methods: The procedure of TTFR was performed on 14 fingers and 4 thumbs of 4 unembalmed cadaveric hands. After the procedures, all fingers and thumbs were dissected and visually assessed.Results: All of the digits and thumbs demonstrated a complete A1 pulley release. There was no injury to the neurovascular bundle (radial digital nerve in case of thumb), flexor tendon, or A2 pulley for each case.Conclusions: The cadaveric study showed that the technique of TTFR was safe and effective, and the future clinical study is necessary to verify the findings of this study.